MiR-25-3p regulates pulmonary arteriovenous malformation after Glenn procedure in patients with univentricular heart via the PHLPP2-HIF-1α axis - Junpei Kawamura; Munekazu Yamakuchi; Kentaro Ueno; Teruto Hashiguchi; Yasuhiro Okamoto (Scientific Reports)
Abstract The detailed mechanism of pulmonary arteriovenous malformations after Glenn surgery (G-PAVMs) in cyanotic congenital heart disease (CHD) remains unclear. Microarray in situ hybridization was performed to assess the miRNA (miRNA) profiles of serum from pediatric patients (0–6 years of age) with G-PAVMs and after the Fontan procedure without G-PAVMs. In addition, we investigated the tube formation, migration, and proliferation of human lung microvascular endothelial cells (HMVEC-L) transfected with miR-25-3p mimic, miR-25-3p inhibitor, or PHLPP2 small interfering RNA, and examined HIF-1α/VEGF-A signaling after hypoxic stimulation. Serum miRNAs that showed ≥ 2-fold higher levels in patients with G-PAVMs than in other patients were selected. MiR-25-3p was significantly upregulated in the pulmonary artery sera of the post-Glenn group than in the post-Fontan group. We identified PHLPP2 as a direct target of miR-25-3p. PHLPP2 expression was significantly decreased in HMVEC-L transfected with miR-25-3p mimic compared to the control cells. HIF-1α and VEGF-A expression levels were increased in HMVEC-L transfected with miR-25-3p mimic compared to the control cells in a PHLPP2/Akt/mTOR signaling-dependent manner after hypoxic stimulation. MiR-25-3p promoted HMVEC-L angiogenesis, proliferation, and migration under hypoxic conditions. MiR-25-3p in the pulmonary arteries may contribute to G-PAVM development.